Theistic humanism and a critique of Wiredu's notion of supernaturalism - Ani, Emmanuel Ifeanyi (Critical research on religion, 2018)
In decrying the evils of supernaturalism, African philosopher Kwasi Wiredu (1931-) proposes humanism, by making concern for human well-being the basis for morality. However, the presentation of humanism as a simple replacement of supernaturalism is objectionable. Wiredu's notion of supernaturalism is too narrow, since it is only a variant of supernaturalism. His reference to humanism is too broad, since humanism is an umbrella of very conflicting worldviews, such as that between secular and theistic humanism. Although Wiredu does not specify which variant of humanism he means, and although he acknowledges that the Akan (the author's tribe in West Africa) believe in a Supreme Being, his general ontology shows that he is closer to the secular than the theistic variant. This article explores the ideological extensions of the two and argues that theistic humanism provides the compatibility needed for being religious and at the same time basing morality on humanistic/naturalistic concerns. In doing so, it distinguishes supernaturalism per se from its ethical and cosmological variants. As a corrective to Wiredu, this article blames these two variants of supernaturalism, rather than supernaturalism per se, for the evils that Wiredu adduces. The conclusion is that in theistic humanism, humanism escapes the dangers of ethical and cosmological supernaturalism without necessarily adopting the antisupernaturalist connotations currently popular with modern secular humanism.